Visual attention for linguistic and non-linguistic body actions in non-signing and native signing children - Bosworth, Rain G.; Hwang, So One; Corina, David P. (Frontiers in Psychology, 2022)
Evidence from adult studies of deaf signers supports the dissociation between neural systems involved in processing visual linguistic and non-linguistic body actions. The question of how and when this specialization arises is poorly understood. Visual attention to these forms is likely to change with age and be affected by prior language experience. The present study used eye-tracking methodology with infants and children as they freely viewed alternating video sequences of lexical American sign language (ASL) signs and non-linguistic body actions (self-directed grooming action and object-directed pantomime). In Experiment 1, we quantified fixation patterns using an area of interest (AOI) approach and calculated face preference index (FPI) values to assess the developmental differences between 6 and 11-month-old hearing infants. Both groups were from monolingual English-speaking homes with no prior exposure to sign language. Six-month-olds attended the signer’s face for grooming; but for mimes and signs, they were drawn to attend to the “articulatory space” where the hands and arms primarily fall. Eleven-month-olds, on the other hand, showed a similar attention to the face for all body action types. We interpret this to reflect an early visual language sensitivity that diminishes with age, just before the child’s first birthday. In Experiment 2, we contrasted 18 hearing monolingual English-speaking children (mean age of 4.8 years) vs. 13 hearing children of deaf adults (CODAs; mean age of 5.7 years) whose primary language at home was ASL. Native signing children had a significantly greater face attentional bias than non-signing children for ASL signs, but not for grooming and mimes. The differences in the visual attention patterns that are contingent on age (in infants) and language experience (in children) may be related to both linguistic specialization over time and the emerging awareness of communicative gestural acts.